Risk Factors Influencing the Occurrence and Severity of Symptomatic Dry Eye Syndrome: A Cross-sectional Study. (2nd November 2021) - Choi, Hye Rin; Kim, Na Hyun; Lee, Ju-Mi; Choi, Dong Phil; Seo, Yuri; Cho, Won Kyung; Song, Jong Suk; Lee, Hyung Keun; Kim, Hyeon Chang
ABSTRACT: Propose : We aimed to investigate the prevalence and risk factors of dry eye syndrome (DES) among a population-based cohort study.Methods : This cross-sectional study was conducted on 475 subjects (184 men and 291 women) enrolled in the Study Group for Environmental Eye Disease at July 2013. Using the ocular surface disease index (OSDI), we measured the DES severity and defined DES as OSDI score ≥13. Current symptoms of DES and possible risk factors such as body mass index, occupations, comorbidities, exercise, smoking and drinking status were assessed by multivariate logistic regression.Results : Prevalence of DES was significantly higher in women (52.6%) than in men (41.9%) ( p < .001). Compared to white-collar workers, blue-collar workers and unemployed persons showed significantly higher DES prevalence and severity. Compared to those with low BMI (<23.0 kg/m 2 ), people with extremely high BMI (≥30.0 kg/m 2 ) had significantly higher odds ratio (OR) of having DES after fully adjusted for sex, age, hypertension, diabetes, menopausal status, hormone replacement therapy, occupation, and lifestyle factors (OR: 2.83, 95% confidence interval: 1.04–7.71).Conclusions : We found some novel factors which have been unknown to the relationship with DES through the five years observation of the cohort. The positive associations of unemployment status, blue-collar work, alcohol habit, and obesity with DES suggests a person's comprehensive condition, not individual factors, contribute significantly in developing DES. Further studies will be helpful to understand the underlying mechanisms.